Criminal Law and Human Rights: Challenges and Enforcement - Deassy J.A. Hehanussa; Carolina Tuhumury; Ardiyanti Aris; Viorizza Suciani Putri; Wahab Aznul Hidaya; Ontran Sumantri (Institute Of computer Science (IOCS), 2024)
Recognising the variety of legal and non-legal tools accessible to react to these challenges within the framework of transitional justice, this research delves into a multi-faceted approach to addressing significant human rights breaches. In both permanent and ad hoc Human Rights tribunals, the primary emphasis is on the function of Truth and Reconciliation Commissions as an alternate or supplementary mechanism to conventional judicial proceedings. This research explores the concept of transitional justice and how it can help victims of human rights violations in the past achieve justice by focusing on truth-telling, reconciliation, and healing. It does this by analysing the dynamics of power transitions from authoritarian to democratic systems. The study's overarching goal is to provide light on the pros and cons of using transitional justice to put an end to egregious human rights abuses and lay the groundwork for long-term social and peace